2006 Conference on Computer Vision and Pattern Recognition Workshop (CVPRW'06)
DOI: 10.1109/cvprw.2006.75
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intensity and Color Corner Detectors for Affine Invariant Salient Regions

Abstract: Global features are commonly used to describe the image content. The problem with this approach is that these features cannot capture all parts of the image having different characteristics. Therefore, local computation of image information is necessary. By using salient points to represent local information, more discriminative features can be computed. This research is based on an existing affine invariant local feature detector, in which the features are assumed to be intensity corners. First, the existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Coleman, Scotney and Kerr [27] adopted an existing edge detection method and extended this work to corner detection using the Linear Gaussian product operator. Sebe et al [8] compared four different algorithms in terms of invariance and distinctiveness of the extracted regions and computational complexity; and proposed a color-based corner detection algorithm.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman, Scotney and Kerr [27] adopted an existing edge detection method and extended this work to corner detection using the Linear Gaussian product operator. Sebe et al [8] compared four different algorithms in terms of invariance and distinctiveness of the extracted regions and computational complexity; and proposed a color-based corner detection algorithm.…”
Section: Related Researchmentioning
confidence: 99%
“…On the other hand, the intensity-based methods estimate a measure to detect corners directly from the Gray values of the original images without a prior segmentation. Rutkowski et al [1], Heyden and Rohr [2], Zheng et al [3], Schmid et al [4], Rockett [5], Tissainayagam and Suter [6], Mokhtarian and Mohanna [7], Sebe et al [8], and Dutta et al [9] provided good literature survey on the existing corner detection algorithms and evaluated their performances.…”
Section: Introductionmentioning
confidence: 99%
“…plain or blurred image regions. To this end, we build on the work in [25], [26] and employ the "Cornerness" of pixels in the image as a measurement of their high-frequency information content. Recall that the "Cornerness", as presented in [25], for a pixel with coordinates u on the image lattice is defined as…”
Section: A Saliency Map Extractionmentioning
confidence: 99%
“…These methods ignore saliency information contained in the color channels. However, it was shown that the distinctiveness of color-based interest points is larger, and therefore color is important when matching images [5]. Furthermore, color plays an important role in the pre-attentive stage in which features are detected [6], [7] as it is one of the elementary stimulus features [8].…”
Section: Introductionmentioning
confidence: 99%